High Sensitivity C-Reactive Protein Level in Children with Congenital Heart Disease: A Single Center Study - Faten Abd el-Aziz; Nevian Nabil Abbas; Hala Ashraf; Rehab Mohammed Elkady; Heba H. Zeid (Pediatric Sciences Journal)
Background: The high sensitivity C-reactive protein (Hs-CRP) is a sensitive acute phase reactant. Hypoxia and asphyxia are known to increase Hs-CRP level. The impact of cyanosis in children with congenital heart disease (CHD) on Hs-CRP values is not known. Aim of the work: to study the effect of cyanosis in children with cyanotic CHD on level of Hs-CRP compared to apparently healthy children. Subjects and Methods: This cross-sectional case-control study included 30 children with CHD as a study group (13 cyanotic and 17 acyanotic) and 30 healthy age and sex matched children as a control group. The study was conducted at the Pediatric Cardiology Clinic, Cairo University Children Hospital, Cairo University Hospitals. All underwent measurement of Hs-CRP using immunoassay technique on COBAS 6000. Results: The mean ± SD age of the included children with CHD and control group was 29.37±37.52 months and 32.60±29.98 months (p=0.097). Females and males comprised 14 (46.7%) and 16(53.3%) of the CHD group and 16 (53.3%) %) and 14 (46.7%) of the control group (p=0.870). The mean ± SD age of acyanotic CHD and oxygen saturation (SpO2) were 55.82 ± 37.51 months and 98.76 ± 0.83% compared to 66.38 ±42.55 months and 87.92 ± 3.76% of the cyanotic CHD (p=0.09), (p=0.51) and (p=0.02) respectively. The mean ± SD Hs-CRP among those with cyanotic, acyanotic and control group was 1.72±3.2, 1.38±2.03 and 0.73±0.41 respectively (p=0.225). The level of Hs-CRP did not correlate with age, birth weight, heart rate, respiratory rate, SpO2, weight percentile, height percentile, hemoglobin level, total leucocytic level, pulmonary artery pressure, ejection fraction (EF), or fractional shortening (FS). Conclusion: Hs-CRP level is not influenced by the underlying CHD whether cyanotic or acyanotic. Hs-CRP diagnostic value is not confounded by cyanosis or SpO2 in children with CHD. The Hs-CRP normal values for healthy children applies to those with CHD whether cyanotic or acyanotic.